Effect of body position on tongue posture in awake patients with obstructive sleep apnoea. Issue 3 (March 1997) - Miyamoto, K; Ozbek, M M; Lowe, A A; Fleetham, J A
Abstract : BACKGROUND: Snoring and obstructive sleep apnoea (OSA) are worse or may only occur in the supine position. The effect of body position on upper airway size has been reported, but the effect on tongue posture has not previously been examined. METHODS: Detailed measurements were made of tongue posture from upright and supine lateral cephalograms on 24 men with OSA and 13 men with non-apnoeic snoring matched for age, body mass index, and craniofacial skeletal pattern. Patients with OSA had apnoea/hypopnoea indices (AHI) of > 50/hour and/or apnoea indices (AI) of > 25/hour while non-apnoeic snorers had AHI of < 10/hour and AI of < 5/hour. RESULTS: In non-apnoeic snorers the tongue depth measurements for the superior-posterior portion of the tongue were larger in the supine than in the upright position (p < 0.05). There was no significant difference in tongue depth measurements between the upright and the supine position in the patients with OSA. CONCLUSIONS: When awake patients with OSA move from the upright to the supine position they maintain their upright tongue posture which may tend to protect against upper airway collapse secondary to the increased gravitational load on the tongue. In contrast, when awake non-apnoeic snorers move from the upright to the supine position a significant dorsal movement in the superior-posterior portion of the tongue is observed.